Insecurity of Schools in Northern Nigeria: Implications for Human Capital Development (Global Journal of Human-Social Science, 2021)
The purpose of this paper was to find out how insecurity of schools in northern Nigeria could be managed to enhance human capital development in the country. The study adopted a descriptive survey design. The population was secondary school teachers and students in northern Nigeria. The sample was 100 teachers and 150 students drawn from the population. Two research questions and two null hypotheses guided the study. The instrument was a researcher developed questionnaire titled Questionnaire on Insecurity of Schools in Northern Nigeria (QISNN). It was structured under four likert scale. It was face and content validated by four experts from two universities in the northern Nigeria, namely; Kaduna state university and federal university Gusau in Zamfara state. The instrument was pilot tested to determine its reliability which yielded a coefficient of 0.78. Direct delivery technique was employed in administering the instrument. Data were analysed using mean and standard deviation and t test statistical analysis.
Keywords: insecurity; schools; northern nigeria; human capital and school children